Criminal Acts of Terrorism and Treason - Muhammad Hisam Hasibuan; Hisam Ahyani (Program Pascasarjana UIN Sumatera Utara Medan, 2020)
Terrorism is a transnational crime that poses a serious threat to national security, public safety, and social stability. It is characterized by the systematic use or threat of violence to create widespread fear and achieve political, ideological, or religious objectives. The increasing complexity of terrorist activities requires not only effective law enforcement but also a comprehensive understanding of the social, political, and economic factors that contribute to radicalization. This study aims to analyze the concept of terrorism, its characteristics, causes, legal regulation, and its impacts on society. The research employs a qualitative approach using a library research method. Data were collected from secondary sources, including scientific books, academic journals, legislation, and other relevant legal documents, particularly Law Number 15 of 2003 concerning Criminal Acts of Terrorism. The collected data were analyzed descriptively and analytically to identify the relationships among concepts and provide a comprehensive understanding of terrorism. The findings indicate that terrorism is an extraordinary crime characterized by organized networks, ideological indoctrination, and strategic acts of violence directed not only at individuals but also at public facilities and state institutions. The study further reveals that terrorism is driven by multiple factors, including social inequality, poverty, political injustice, weak governance, identity conflicts, and religious radicalism. Its impacts extend beyond physical destruction, affecting political stability, economic development, public trust, and psychological well-being. Indonesian law has established a legal framework to combat terrorism through criminal sanctions and preventive measures; however, legal action alone is insufficient. Effective counterterrorism requires an integrated strategy that combines law enforcement, education, poverty reduction, promotion of religious moderation, community participation, and inter-agency cooperation. Such a comprehensive approach is essential to strengthen national resilience, prevent radicalization, and ensure long-term peace and security.